Effects of inflammatory mediators on bone marrow mesenchymal stem cells - Marsh, Sarah A. (2019)
Despite osteoarthritis (OA) being the most prevalent form of joint disease, there is a striking unmet need for treatment strategies, with current treatments focused on the relief of pain symptoms. The inherent properties of mesenchymal stem cells (MSCs) make them an attractive candidate for a novel transplantation strategy, as they have both the potential to differentiate into chondrocytes for replacement of degraded cartilage, and the potential to exert immunosuppressive effects for modulation of the inflammatory environment. However, the inflammatory environment of the joint may affect the ability of these cells to functionally integrate into the host tissue and exert beneficial effects, as indicated by a lack of success seen in clinical trials. Identification of factors and cell signalling pathways that influence MSC function is therefore critical for ensuring their success in the clinic, and so this in vitro project aimed to identify the effects of inflammatory mediators on bone marrow MSCs (BMSCs). To investigate this, BMSCs were cultured in the presence of inflammatory mediators associated with OA pathology (IL-1β, IL-8, IL-10, MCP-1, NGF), either individually or in combination. Results showed that conditions containing IL-1β significantly affected the differentiation response of these cells under chondrogenic and osteogenic conditions. Gene expression analysis revealed changes in MAPK, Wnt and TLR signalling pathways, and highlighted the increased expression of pro-inflammatory cytokines and cartilage degrading enzymes. This work provides a basis for further investigation into factors present in the OA joint that may limit the therapeutic potential of MSCs, supporting further research into ways to circumvent this for novel OA treatments.